Textured Vn Coatings with Ag3vo4 Solid Lubricant Reservoirs - Singh, D (2011)
Silver oxovanadate powders were produced using a low temperature hydrothermal synthesis method. X-ray diffraction (XRD) and Raman microscopy revealed the formation of the ?-Ag3VO4 phase, and differential scanning calorimetry (DSC) indicated that the powders underwent phase changes with the increase of temperature (formation of Ag-deficient phases). Ag3VO4 precipitates were subsequently investigated as potential high temperature solid lubricant (SL) powders that may be burnished onto textured surfaces. Textured coatings were produced by the sputter deposition of vanadium nitride (VN) thin films, followed by the fabrication of a periodic array of micro-scale dimples with reactive ion etching (RIE). The etched patterns acted as reservoirs to replenish the sliding contact with solid lubricants. The effectiveness of this new design of high temperature tribological coating was tested using a pin-on-desk tribotester. A significant decrease in the wear rate and coefficient of friction (CoF) was achieved at high temperatures (750°C) and was maintained as a result of the storage of the Ag3VO4 phase in the dimples. After wear testing, Raman spectroscopy and XRD were used to identify the phase composition developed as a result of tribotesting. It was found that the burnished powders were more effective in enhancing the tribological properties of textured films compared to burnished/un-burnished monolithic VN coatings. © 2011 Elsevier B.V.